Analisis Sistem E-Procurement Pengadaan Barang Dan Jasa - Diva Sukma Az-zahra; Yurni Fadhillah; Aisah Yuningsih; Sigit Djalu Purwoko (Jurnal Kajian dan Penelitian Umum, 2024)
This research provides a comprehensive analysis of e-procurement systems in the procurement of goods and services. In the digital era, technological advances have brought significant transformations, especially in the procurement process. This study explores the concept of e-procurement which refers to the online procurement process. The research methodology used is qualitative, using an inductive approach to gain a deeper understanding of the subject matter. The study discusses in detail the principles of e-procurement, the standard procedures involved in procuring goods and services, and the various benefits of the e-procurement process. It also evaluates the effectiveness of e- procurement in the procurement of goods and services. The study concludes that e- procurement, by harnessing the power of technology, greatly simplifies the procurement process. This simplification results in financial savings, time efficiency, and labor reduction, thereby improving the overall effectiveness of the procurement process.